Americanizing the movies and "movie-mad" audiences, 1910-1914 - Abel, Richard, 1941- (University of California Press, 2006)
This engaging, deeply researched study provides the richest and most nuanced picture we have to date of cinema - both movies and movie-going - in the early 1910s. At the same time, it makes clear the profound relationship between early cinema and the construction of a national identity in this important transitional period in the United States. Abel sheds new light on the history of the film industry, on working-class and immigrant culture at the turn of the century, and on the process of imaging a national community.